The Influence of G.H.A. Juynboll’s Hadith Thought on Hadith Studies - Setiawan, Ahmad Siddiq; Siti Aisyah Kara; Zulfahmi Alwi (el-Sunnah: Jurnal Kajian Hadis dan Integrasi Ilmu, 2025)
This article examines G.H.A. Juynboll's thoughts on hadith and their implications for hadith research. This study employs a library research method, using books and articles as primary references for data sources. The results and discussion reveal that Juynboll's thoughts have significantly influenced hadith studies, including: 1) Juynboll's hadith research methods have affected the outcomes of hadith studies conducted by scholars and academics. His views on the ideal transmission chain, as outlined in his common link theory, have drawn considerable criticism from various circles; 2) Juynboll's critique of the jarh wa ta’dil system in hadith research stems from his limited understanding of the information he gathered, leading him to perceive the credibility assessments of narrators by scholars as arbitrary and influenced by subjectivity towards certain narrators; 3) Juynboll's argument to undermine the golden chain by questioning the historicity of Nāfi‘ as a hadith narrator was refuted by Harald Motzki, who demonstrated that Juynboll's shortcomings in collecting historical data were due to his limited comprehension of the aspects inherent in the information he encountered.